Paul Luykx, Heraut van de katholieke herleving. Gerard Brom 1882-1959 - van den Bos, Maarten (BMGN - Low Countries Historical Review, 2016)
Paul Luykx, Heraut van de katholieke herleving. Gerard Brom 1882-1959 (Nijmegen: Vantilt, 2015, 956 pp., isbn 978 94 6004 200 3).